Conceptual and Institutional Aspects of EU Energy Policy (1990-2014) - Y. V. Borovskiy; K. V. Trachuk (Vestnik MGIMO-Universiteta)
Ideological and institutional framework of the European energy policy, which is still work in progress, is crucial to the EU as it faces new political and economic challenges related to the recent Ukrainian crisis. Even if key energy policy issues are still decided by member states as the EU only seeks to speak with one voice in energy matters externally, much progress has been made over the last two decades in terms of the EU's energy policy formulation and institutional development. The Lisbon Treaty made the energy policy a sphere of "shared competence" of EU institutions and member states. The European Commission's numerous policy documents ("White" and "Green books" 1995, 2000 and 2006) provided a basis for the development of an integrated energy market. Substantial progress has been achieved in the area of energy policy harmonization between the EU and neighboring countries (Energy Charter Treaty, European Energy Community). The Union's key energy policy areas also included supply diversification (trans-European energy networks), development of unconventional energy production, climate change and energy efficiency. Over the last decade climate changes has become a cornerstone of EU energy policy and is regarded by the EU as key to moderating energy demand and reducing import dependency.